2021
DOI: 10.3390/pathogens10060703
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Sputum Impairs the Ability of Neutrophils to Kill Staphylococcus aureus

Abstract: Cystic fibrosis (CF) airway disease is characterized by chronic microbial infections and infiltration of inflammatory polymorphonuclear (PMN) granulocytes. Staphylococcus aureus (S. aureus) is a major lung pathogen in CF that persists despite the presence of PMNs and has been associated with CF lung function decline. While PMNs represent the main mechanism of the immune system to kill S. aureus, it remains largely unknown why PMNs fail to eliminate S. aureus in CF. The goal of this study was to observe how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Our previous results demonstrated that PMNs isolated from PwCF killed MRSA CF clinical isolates to the same extent as PMNs derived from healthy individuals [10] To further confirm this observation, we recruited additional PwCF and age-and sex-matched healthy donors, and obtained the same result (Figure 1A). Additionally, we noticed that PMNmediated killing of only the reference strain, USA300, was impaired in PwCF (Figure 1A).…”
Section: Cf Sputum Treatment Impairs Cf Pmns' Ability To Kill Mrsasupporting
confidence: 69%
See 2 more Smart Citations
“…Our previous results demonstrated that PMNs isolated from PwCF killed MRSA CF clinical isolates to the same extent as PMNs derived from healthy individuals [10] To further confirm this observation, we recruited additional PwCF and age-and sex-matched healthy donors, and obtained the same result (Figure 1A). Additionally, we noticed that PMNmediated killing of only the reference strain, USA300, was impaired in PwCF (Figure 1A).…”
Section: Cf Sputum Treatment Impairs Cf Pmns' Ability To Kill Mrsasupporting
confidence: 69%
“…Overall, we propose that MRSA is predominantly killed in healthy PMNs via phagocytosis-initiated intracellular mechanisms. We have also shown previously that CF sputum impaired the ability of PMNs lated from healthy donors to kill CF clinical isolates of MRSA [10]. Next, we explo whether CF sputum had similar effects on PMNs isolated from the blood of PwCF, as w PMNs from PwCF were first exposed to the CF sputum cocktail and then infected w MRSA, according to our standard protocol.…”
Section: Mrsa Killing By Pmns Is Predominantly Mediated By Phagocytos...mentioning
confidence: 83%
See 1 more Smart Citation
“…In fact, EVs can be generated from all of the cells present in the CF lung including, but not limited to the neutrophils and epithelial cells, such as macrophages, monocytes, T‐cells, as well as bacteria and fungus 42 . There have been recent studies that EVs from neutrophils can cause activation of other neutrophils, 43 and that EVs from S. aureus can down‐regulate the ability of neutrophils to kill bacterial pathogens 44 . EVs from CFTR‐mutated epithelial cells were able to activate neutrophils 45 and our study now documents communication in the other direction, that is, from neutrophils to epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…42 There have been recent studies that EVs from neutrophils can cause activation of other neutrophils, 43 and that EVs from S. aureus can down-regulate the ability of neutrophils to kill bacterial pathogens. 44 EVs from CFTR-mutated epithelial cells were able to activate neutrophils 45…”
Section: Evs Contribute To Sustained Inflammasome Signaling Between R...mentioning
confidence: 99%